Marriage in the Mother City: The Anglican marriage records of Cape Town, 1865-1960 - Fourie, Johan; Rommelspacher, Amy (School for Basic Sciences, North-West University, Vaal Triangle Campus, Vanderbijlpark, 2021)
As a social institution that permeates almost all societies, marriage trends and practices are studied across the social sciences. Yet South African marriages, past and present, remain understudied, notably because of a lack of adequate source material. This paper contributes to a better understanding of marriage trends in the South African past by offering a new dataset of more than 55 000 marriages solemnized in the Anglican church of Cape Town between 1865 and 1960. We show how these records can both reveal new evidence to test existing hypotheses and expose trends that open new questions for historical inquiry.
Keywords: Marriages; Church; Parish; Marriage trends; Anglican; Cape Town; South-Africa